Needlestick and sharp injuries among health care workers in Saudi hospitals: a review - AbdulrahmanA., Al Johani; Karuppiah, Karmegam; K.C. Mani, Kulanthayan; Alya O., Al Mutairi; Sambasivam, Sivasankar (Malaysian Public Health Physicians Association, 2016)
This paper explains Needlestick and Sharp Injuries among Healthcare Workers in Saudi Hospitals. Presently there are number of factors that are responsible for health care workers injuries. Lack of secure environment and ignorance to safety measures can lead to injuries due to Needlestick and Sharp objects. There is a significant need of providing better working environment for health care workers in Saudi Arabia. Following daily practices and World Health Organization’s measures for taking the preventive steps for these injuries is necessary. Trying to avoid utilizing needles whenever secure and efficient substitutes are present, providing needle containers, avoiding re-capping and wearing gloves on both hands are some of the measures that could be taken to make sure these problems do not recur.